Assessment of Patient Knowledge Level Towards MRI Safety Before the Scanning in Saudi Arabia - Alahmari,Dhafer; Alsahli,Fahad M; Alghamdi,Sami A; Alomair,Othman I; Alghamdi,Abdulrahman; Alsaadi,Mohammed J (International Journal of General Medicine, 2022)
Dhafer M Alahmari,1 Fahad M Alsahli,1 Sami A Alghamdi,2 Othman I Alomair,2 Abdulrahman Alghamdi,3 Mohammed J Alsaadi4 1Department of Medical Imaging, King Saud Medical City, Riyadh, Saudi Arabia; 2Department of Radiological Sciences, College of Applied Medical Sciences, King Saud University, Riyadh, Saudi Arabia; 3Department of Medical Imaging, Aseer Central Hospital, Abha, Saudi Arabia; 4Department of Radiology and Medical Imaging, College of Applied Medical Sciences, Prince Sattam Bin Abdulaziz University, Al-Kharj, Saudi ArabiaCorrespondence: Mohammed J Alsaadi, Department of Radiology and Medical Imaging, College of Applied Medical Sciences, Prince Sattam bin Abdulaziz University, 145, PO Box 422, Al-Kharj, 11942, Saudi Arabia, Tel +00966541001006, Email m.alsaadi@psau.edu.saPurpose: Magnetic resonance imaging (MRI) is an important diagnostic method in modern clinical medicine. Patients’ ‎‎knowledge about MRI is of utmost importance for optimizing the workflow, ‎safety, and patient comfort and saving valuable time for the MRI department. This study investigates patient knowledge levels regarding MRI safety before an MRI examination.Patients and Methods: A cross-sectional survey was completed by 200 patients who required MRI. Recruitment occurred over eight weeks in ‎governmental and private hospitals in Saudi ‎Arabia; both hospitals and participants were selected randomly. The ‎questionnaire was given to the patients prior to ‎their MRI scans. Descriptive statistics and chi-square tests were performed to identify relationships between knowledge of MRI safety and selected demographic groupings (age, gender, education level, income level). It also evaluates their source of information and assesses the patient’s previous experience regarding MRI scans.&#x200EResults: The study sample consisted of 200 patients from 230 surveys distributed in ‎Saudi Arabia, and the response rate was ∼ 87%. Depending on the P-values of the chi-square statistical test to find the relationship between ...